2021
DOI: 10.47127/ijtmr.v6i2.124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Social Capital on SMEs Performance: Does Innovation Matter

Abstract: The study investigated how social capital influences firms to generate higher performance through innovation among SMEs in Ghana. The study employed a quantitative approach. The study employed stratified sampling to sample 240 respondents from 240 SMEs in the Eastern Region of Ghana. Primary data was gathered using a questionnaire adapted from previously validated instruments. The data gathered was analyzed using Partial Least Square (PLS) of the Structural Equation Model (SEM). The findings proved internal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(60 reference statements)
1
1
0
Order By: Relevance
“…This shows that the better the business owners are in networking with various groups, the more insightful the business owners are to continue to innovate so that they can open up marketing opportunities and open up new methods of running their business. The results of this study are in line with previous research which reveals that social capital affects innovative work behaviour(Faisol et al, 2022;Kamewor, Mohammed, & Teye, 2021;Pham et al, 2022).…”
supporting
confidence: 93%
“…This shows that the better the business owners are in networking with various groups, the more insightful the business owners are to continue to innovate so that they can open up marketing opportunities and open up new methods of running their business. The results of this study are in line with previous research which reveals that social capital affects innovative work behaviour(Faisol et al, 2022;Kamewor, Mohammed, & Teye, 2021;Pham et al, 2022).…”
supporting
confidence: 93%
“…Agyapong et al (2017) conducted a study that confirmed the positive relationship between social capital and performance and revealed innovation's mediating role in this relationship. Kamewor et al (2021) further supported these findings by showing the positive and significant impact of social capital on innovation practices among SMEs in Ghana and concluded that the effect of social capital on firm performance is indirectly through the level of innovation practices. Bosma et al (2004) investigated the impact of human and social capital investment on entrepreneurial performance.…”
Section: Relationship Between Social Capital and Business Performance...mentioning
confidence: 55%